(untitled) (SJ Ophthalmology Africa, 2025)
Abstract Background Age-related macular degeneration causes irreversible blindness. Two types of Age-related Macular Degenerations are Wet macular degeneration and Dry macular degeneration. The study aims to assess the aim of the study is to assess the Age and social related Risk factors for Age-Related Macular Degeneration. Methodology A Cross-sectional descriptive study design involving quantitative methods of data collection, The study population comprised of all patients receiving eye care services for Age-related Macular Degeneration conditions at the eye unit of Jinja Regional Referral Hospital for a period of 6 months from October 2022 to March 2023. Non-probability sampling was used to select 50 participants. Results The majority of 29/50 (58%) respondents were females and 21/50 (42%) males. Most 39/50 (78%) of the respondents lived in Rural areas while a lower number 11/50 (22%) lived in Urban areas. The majority 25/50 (50%) were between 61-70 years, followed by respondents 14/50 (28%) who were between 51-60 years, followed by respondents 2/50 (4%) which were 41-50 years while the least were respondents 2/50 (4%). Most 24/50(48%) strongly agreed that smoking is a risk factor for Age-related Macular Degeneration. 32/50 (64%) took alcohol while18/50 (36%) did not take alcohol. Conclusion The significant risk factors for Age-related Macular Degenerations were, increasing age groups of 61-70 years and 51-60 years, smoking, and low level of education. Recommendations The Government should sensitize people on the risk factors for Age related Macular Degenerations. At the same time, the Government should set up more eye clinics to increase accessibility to eye care services.